DAMPAK PENAMBAHAN CHELATING AGENT (ASAM ASETAT,ASAM SITRAT DAN JERUK NIPIS) TERHADAP KADAR Fe, Zn DAN PROTEIN DAGING KUPANG BERAS (Corbula faba) - Indasah, Indasah (STRADA : Jurnal Ilmiah Kesehatan, 2012)
The objective of this research is to study the use of chelating agent (acetic acid, citric acid and lime fruit) by having minimal decrease of Fe, Zn and protein of kupang beras (Corbula faba).The research is True Experimental and used is Completely Randomized Design with 9 treatments, namely, the addition of 5 %, 15 % and 25 % acetic acid, 5.3 %, 16 % and 26.6 % citric acid, 79 gram, 238 gram and 396 gram lime fruit and compared with controlled treatment.The data obtained from the research finding show that without treatment (control) the average content of Fe is 447.651 ppm, Zn is 14.404 ppm and protein is 6.603 %. The research findings show that by adding acetic acid there is decrease of Fe by 40 – 44.8 %, a decrease of Zn by 78 – 87.7 % and a protein decrease by 30.4 – 36.3 %. The research findings show that by adding citric acid there is decrease of f Fe by 38.9 – 49 %, a decrease of Zn by 81 – 85.8 % and a protein decrease by 24.4 – 33.9 %. The research findings show that by adding lime there is decrease of Fe by 39.6 – 45.2 %, a decrease of Zn by 81.5 – 83.2 % and a protein decrease by 23.2 – 28.7 %.